Introducing database reliability engineering - Campbell, Laine; Majors, Charity (O'Reilly Media, 2018)
In this lesson, you'll learn the guiding principles of excellent database reliability engineering. You can apply this framework of practices for designing, building, and operating data stores to any database technology or environment.